Publishing for the Chair by the Chair - Trey Guinn (Academic Chairpersons Conference Proceedings, 2020)
Many argue that publishing likely suffers and creativity may be stifled during an administrative appointment, such as serving in the role of Academic Chair. But this does not need to be the case. In this discussion-based lunch, we look at how to capitalize on new opportunities for creative work and publishing. Join for lunch, learn some ideas, share some ideas too!
Keywords: Creativity; Publishing; Managing Scholarship; Maximizing Position